2015
DOI: 10.2527/jas.2014-8507
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modeling of feed intake

Abstract: With the development of automatic self-feeders and electronic identification, automated, repeated measurements of individual feed intake (FI) and BW are becoming available in more species. Consequently, genetic models for longitudinal data need to be applied to study FI or related traits. To handle this type of data, several flexible mixed-model approaches exist such as character process (CPr), structured antedependence (SAD), or random regression (RR) models. The objective of this study was to compare how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Comparison of AIC values showed that the multiple-trait SAD model provided a better fit to the data than the RR model in both species. The same conclusion has been drawn in previous studies on other traits [8, 9]. Results obtained with RR models were essentially consistent with those of the multiple-trait SAD model, which enables us to be confident in the estimations obtained with the SAD approach.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Comparison of AIC values showed that the multiple-trait SAD model provided a better fit to the data than the RR model in both species. The same conclusion has been drawn in previous studies on other traits [8, 9]. Results obtained with RR models were essentially consistent with those of the multiple-trait SAD model, which enables us to be confident in the estimations obtained with the SAD approach.…”
Section: Discussionsupporting
confidence: 89%
“…A single-trait SAD model is then defined by the order of the antedependence (), the degree of the polynomial for each antedependence parameter ( to ), and the degree of the polynomial for the innovation variance () for each random effect. We will refer to single-trait SAD models as SAD [8]. For instance SAD 111 stands for a SAD model with: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Danish pig breeding, Duroc is a terminal sire line with strong selection pressure for feed efficiency, growth, and lean meat production; however, Landrace and Yorkshire are dam line breeds with the primary selection objective of improvement in maternal traits but still a substantial emphasis on feed efficiency and growth. Figure 1 shows smooth results also towards the borders of the data, suggesting no border effects, which are sometimes seen in random regression models using Legendre polynomials, for example, David et al (2015). Cai et al (2011) reported heritabilities of 0.10 to 0.37 for daily FI during the test period using random regression with second-order Legendre polynomials of age in boars of Yorkshire pigs.…”
Section: Genetic Background Of Feed Intakementioning
confidence: 82%
“…Conversely, the direct and indirect genetic effects were correlated , where is the 10 × 10 (co)variance matrix for the genetic effects (5 weeks for the direct genetic effects and 5 weeks for the indirect genetic effects) and is the additive relationship matrix based on pedigree. Possible non-null covariances between random effects at different times were taken into account using a SAD approach [ 16 – 18 ]. It should be noted that this model does not include a residual term to help convergence and to avoid identifiability problems between structured permanent and classical residual covariance matrices [ 19 ], as in previous studies using the SAD approach [ 15 , 17 ].…”
Section: Methodsmentioning
confidence: 99%